A Magician's Tale - Makeda Semret; Angeline Law; Stephen Turner; Benoit de Varennes; Brian J Ward; Thao Huynh (Canadian Journal of Infectious Diseases and Medical Microbiology)
Case presentation A 19-year-old male university student and part-time magician presented with a two-week history of fever with rigors, nausea, vomiting, headaches and migrating polyarthralgia. The patient's medical history was significant for a childhood murmur that was presumed benign. The patient denied use of illicit drugs and was not on any medication at the time of presentation. The patient owned several pets, including a dog, a monitor lizard and rabbits used for his magic tricks.